Olympic Women and the Media
XI, 260 p.
Keywords: This book examines how women athletes were represented in international media coverage during the 2004 Olympic Games. Through feminist theorizing and qualitative textual analysis, the contributors discuss sexualization, nationalism, success, failure and the [in]visibility of women athletes in newspaper reporting in Asia, Europe and the USA.